Theoretical investigations for hydrogen storage properties improvement in metal-organic frameworks and new bi-dimensional systems - Majid EL Kassaoui (Faculté des Sciences de Rabat, 2021)
With the exponential increase in demand for effective and renewable energy, the hydrogen era has begun. Hydrogen energy is an ideal candidate to replace fossil fuels due to its high energy density, ease of availability and zero carbon emission. However, the development of a suitable storage media is the biggest challenge toward the realization of a H2 based mobility applications. To date, the common H2 storage practices are exclusively in the form of high-pressure gas cylinders and liquid hydrogen, which prevent its applications due to safety concerns and socio-economic constraints. Therefore, H2 storage on solid materials via physisorption is an ingenious alternative. We study two interesting axes in hydrogen storage materials. The first is a new approach aimed at tuning the hydrogen storage properties of metal organic frameworks type MOF-5. Based on this, we show that our system may reach a maximum gravimetric storage capacity of 4.09 wt% for multiple hydrogen molecules. Moreover, the decoration of Li, Be and Na combined to the substitution, shows an exceptional improvement of hydrogen storage properties. In the second axis, ab initio calculations have been also applied to study the potential of t-graphene-like boron nitride (t-B4N4) and beryllium carbide (Be2C) as a new 2D material for hydrogen storage. Our results show that the adsorption energy of H2 on the Li-decorated t-B4N4/Be2C monolayer is appropriate for hydrogen storage, with a maximum gravimetric capacity of 12.47 wt% and 10.21 wt% for t-B4N4 and Be2C, respectively. In addition, the desorption temperature estimates were validated by AIMD simulations of hydrogenated Li@t-B4N4 and Li@Be2C. To summarize, these materials are interesting candidates for hydrogen storage due to their promising hydrogenation properties
Études théoriques pour l'amélioration des propriétés de stockage de l'hydrogène dans les matériaux organo-métalliques et les nouveaux systèmes bidimensionnels
Keywords: Hydrogen storage; Metal; organic framework; 5; 2D materials; Ab initio calculations; AIMD; Adsorption; Metal functionalization.; Physique Informatique